The Participation Based On Article 6 Of The Ministry Of Home Affairs Regulation Number 111 Of 2014 Form The Perspective Of Siyasah Tanfiziyyah - Derie Andargo; Linda Firdawaty; Arif Fikri (IBN KHALDUN BOGOR, 2025)
Community participation is a process where the interests, needs, and values of the community are incorporated into government decision-making. This involves two-way communication and dialogue, with the primary goal of achieving better decision-making and community support. To understand community participation in the formation of village regulations, this research is important as it aims to address two main issues: First, how community participation in the formation of village regulations in Bumi Aji Village, Central Lampung, is implemented based on Article 6 of the Ministry of Home Affairs Regulation Number 111 of 2014; and second, how the SiyasahTanfiżiyyah perspective reviews the role of community participation in the formation of village regulations in Bumi Aji Village. The role of the community in Bumi Aji Village, Central Lampung, is examined using the SiyāsahTanfiżiyyah perspective approach, alongside the method used, which is field research with a descriptive qualitative approach, and the nature of the research is descriptive analytical. The research results show that community participation in Bumi Aji Village runs in accordance with the guidelines of the Ministry of Home Affairs Regulation Number 111 of 2014, which aligns with the principles of Siyāsah Tanfiżiyyah because obeying the applicable law is a form of state obedience.